Motion planning for autonomous lane change manoeuvre with abort ability - Chandru, Rajashekar; Selvaraj, Yuvaraj (My University, 2016)
The field of highly autonomous ground vehicle systems has been the focus of research in both, academia and industry in the recent decades and is expected to be so in the near future. The work in this thesis focuses on one aspect of highly autonomous vehicles - motion planning in complex traffic environments. The scope of this thesis is limited to motion planning for autonomous lane change and lane change abortion manoeuvres in dense urban traffic scenarios. The purpose of the work is to tackle the problem of autonomous lane change driving in uncertain traffic environments where the vehicle has to anticipate and adapt to behaviour of the surrounding vehicles. The solution is presented as a robust algorithm which is tolerant to uncertainties in the planning horizon. Safety is guaranteed by modelling the safety critical areas around the surrounding vehicles which the autonomous vehicle should not enter in order to plan an evasive action. The problem of motion planning during the entire manoeuvre is solved as two loosely coupled problems. A longitudinal trajectory is first planned and then for a given longitudinal trajectory, the lateral motion is planned with respect to the safety constraints using Model Predictive Control (MPC). The proposed solution is then evaluated for a series of scenarios in a simulation environment modeled using MATLAB/Simulink. Different unexpected behaviours of the surrounding vehicles are simulated and the results show that the proposed algorithm is capable of handling the simulated scenarios. The thesis is concluded with discussions on the results and possible future extension of the work carried out in this thesis.
Keywords: Elektroteknik och elektronik; Electrical Engineering, Electronic Engineering, Information Engineering